Penempatan Phasor Measurement Unit untuk Menentukan Prediksi Margin Kestabilan Tegangan - Levin Halim; Nanang Hariyanto; Muhammad Nurdin (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2019)
The development of power system in new transmission and generation facilities has burdened the power system more than before. As a consequence, many power systems are facing voltage problems which will lead to voltage instability. This paper discusses the placement of Phasor Measurement Unit (PMU) which utilizes integer linear programming to determine voltage stability margin (VSM) prediction based on local measurement which using thevenin equivalent to represent the power system. The PMU placement is chosen in such way so that the voltage and current phasor at each bus of the power system is observable. Those obtained voltage and current phasor data then will be utilized to determine the voltage stability margin prediction.